TÁRBIYA SABAǴÍNDA OQÍWSHÍLARDÍŃ KREATIV PIKIRLEWIN RAWAJLANDÍRÍW - Allashova, N. (SCIENCE and SOCIETY, 2025)
This article is devoted to the issues of developing students’ creativity through interactive methods in elementary grades.